2010
DOI: 10.1155/2010/521457
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency—A Clinical Spectrum: Is There a Symptomatic Nonosteomalacic State?

Abstract: Vitamin D deficiency is not uncommon even in the sunny land of India. Lack of sun exposure and inadequate oral intake are both responsible for vitamin D deficiency. This article provides a retrospective, examining the effects of Vitamin D deficiency in 71 patients. The study's inclusion criterion was low vitamin D level combined with musculoskeletal symptoms but without the presence of osteomalacia. All patients in this study were suspected to have vitamin D deficiency. The data were retrieved from the case-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…A recent Indian study has also reported that a large chunk of hypovitaminosis D is subclinical, characterised by non-specific musculoskeletal symptoms as the only manifestation. The same study also concludes that hypovitaminosis D affects individuals in the prime of their life and affects the quality of life and the productivity of those suffering from it 28. Another limitation of our study was not assessing the functional relevance of hypovitaminosis D.…”
Section: Discussionmentioning
confidence: 73%
“…A recent Indian study has also reported that a large chunk of hypovitaminosis D is subclinical, characterised by non-specific musculoskeletal symptoms as the only manifestation. The same study also concludes that hypovitaminosis D affects individuals in the prime of their life and affects the quality of life and the productivity of those suffering from it 28. Another limitation of our study was not assessing the functional relevance of hypovitaminosis D.…”
Section: Discussionmentioning
confidence: 73%
“…Serum 25 (OH) D is a potent indicator of total body vitamin D, the main regulator hormone in calcium and vitamin D metabolism. [9] Vitamin D deficiency may be without florid signs like bone tenderness in around 63 % patients, [10] an important finding, as without bony tenderness and without proper awareness on the part of physicians, vitamin D deficiency can easily be overlooked. Severe vitamin D deficiency causes a reversible myopathy characterized by muscle weakness, wasting, and instability of gait.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, vitamin D deficiency results in abnormalities in bone metabolism known as rickets, osteomalacia, and osteoporosis ( 2 , 3 ). On the other hand, it is associated with non-skeletal diseases such as type one diabetes mellitus ( 2 , 4 , 5 ), multiple sclerosis ( 2 ), cancer ( 2 , 5 ), hypertension ( 5 ) or cardiovascular disease ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%